Microalgal biotechnology : integration and economy - Posten, Clemens; Walter, Christian, 1965 December 15- (Walter de Gruyter, 2012)
With the high interest in renewable resources, the field of algal biotechnology has undergone a huge leap in importance in recent years. The book Microalgae Biotechnology - Integration and Economy treats integrated approaches to bring the high potential of microalgae into application, accelerate the development of really working production processes and put finally the products on the market. Close interaction of biology and process engineering becomes visible in the described processes. The big impact of microalgal biotechnology on our future society is outlined as a desirable consequence of scientific progress. This book will allow protagonists in academia and industry as well as decision makers in industry and politics to get a clear picture of current possibilities and future trends in microalgal biotechnology.